A composite material and a method of making and use thereof
Patent Information
- Application Number
- CN202410636548.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-05-22
AI Technical Summary
本申请中所述复合材料解决了现有技术中吸附材料无法兼顾良好的耐水性和对药物异构体的分离能力和保留时间的问题
[0032]本发明中,发明人针对传统SiO2吸附材料耐水性差、离子交换能力低、对药物异构体的分离能力弱、保留时间短等问题,使用MOFs作为吸附材料。同时,针对MOFs材料在液相中易局部或整体坍塌和动态吸附效率差的技术问题,申请人提供了一种复合材料及其制备方法和用途,所述复合材料为表面复合有球形多孔碳的Cu-BTC晶体,具有高分子识别性、高选择性、高吸附容量、高耐水性、对环境友好;制备过程简单,经济环保满足研究和应用需求。
Smart Images

Figure CN118437285B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials, and in particular to a composite material, its preparation method, and its uses. Background Technology
[0002] In the pharmaceutical field, most drug molecules have isomer structures, and different isomers often exhibit different pharmacological effects. When isomeric drugs enter the body, they generally exert their effects through the matching and molecular recognition between the drug and its target molecules. Some drug molecules have only one isomer with pharmacological effects, while the other isomer is ineffective. For example, D-phenylisopropylamine is a very effective central nervous system stimulant, while L-phenylisopropylamine has almost no effect. The L-isomer of propranolol is 100 times more bioactive than the D-isomer. Some chiral drugs exhibit different pharmacological effects when their two isomers are different; for example, the S-isomer of tretoguinol is a bronchodilator, while the R-isomer inhibits platelet aggregation. Some drug molecules even have one isomer that can cause toxic side effects. For another example, vitamin E, also known as tocopherol, usually exists in nature in four forms: α-, β-, γ-, and δ-tocopherol. All are benzodihydropyran derivatives, differing only slightly in the position of the methyl group on the side chain. Different tocopherols have similar structures but significantly different properties; for example, the antioxidant capacity and biological activity of different tocopherols are exactly opposite in order. Another typical example is sialic acid glycans distributed on the surface of mammalian cells or some secretory proteins. This outermost position and widespread distribution make sialic acid glycans play an important role in viral infection, immune response, and cancer development. However, due to the complex composition of sialic acid glycans, diverse linkage forms, and even the existence of linkage isomers, their identification and structural analysis are very difficult. Qing Guangyan et al. grafted polymers with sugar recognition responsiveness into the interior of nanochannels, using different glycans to induce polymer contraction, thereby causing different degrees of "OFF-ON" changes in the nanochannels and recognizable changes in the output ion current, achieving the identification and differentiation of different glycan linkage isomers. However, the molecular recognition efficiency, separation degree, and mechanism remain unclear and require further in-depth research. Traditional adsorbent materials such as SiO2 have drawbacks including poor alkali resistance, low ion exchange capacity, poor chemical stability of modified silica gel, weak separation ability of drug isomers, and short retention time. Therefore, there is an urgent need to develop a novel adsorbent material for highly efficient molecular recognition of drug isomers.
[0003] MOFs (Metal-Organic Facility Materials) are a new class of porous materials that have attracted considerable attention in recent years due to their large specific surface area, tunable pore size, and diverse types of unsaturated metal centers, and have been applied in the field of dye adsorption. However, the adsorption application of MOFs in the liquid phase currently faces two major challenges: First, MOFs have poor resistance to water, while water has a stronger nucleophilicity than organic ligands. Water can disrupt the metal bonds on MOFs, exposing them and causing coordination with water, resulting in partial or overall collapse of the MOFs and affecting their adsorption application in the liquid phase. Second, the microporous characteristics of MOFs will reduce their dynamic adsorption efficiency in aqueous solutions. Summary of the Invention
[0004] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a composite material, its preparation method, and its uses. The composite material described in this application solves the problem that existing adsorbent materials cannot simultaneously achieve good water resistance and separation ability and retention time for drug isomers.
[0005] To achieve the above and other related objectives, the present invention is obtained through the following technical solution.
[0006] The first aspect of the present invention discloses a composite material, wherein the composite material is porous particles, and the porous particles are Cu-BTC crystals with spherical porous carbon composited on the surface.
[0007] Preferably, the specific surface area of the composite material is 900–1500 m². 2 / g. The higher the specific surface area of the composite material, the more active sites it exhibits, thus enhancing the adsorption capacity of RhB.
[0008] Preferably, the average pore size of the composite material is 0.5–1.1 nm, such as 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, or 1.1 nm. The composite material has a relatively large pore size and a wide pore size distribution range, which is beneficial for the diffusion of RhB macromolecules during the adsorption process.
[0009] Preferably, the pore volume of the composite material is 0.5–0.6 cm. 3 / g, such as 0.5cm 3 / g, 0.51cm 3 / g, 0.52cm 3 / g, 0.53cm 3 / g, 0.54cm 3 / g, 0.55cm 3 / g, 0.56cm 3 / g, 0.57cm 3 / g, 0.58cm 3 / g, 0.59cm 3 / g, 0.6cm 3 / g.
[0010] Preferably, the particle size of a single spherical porous carbon is 100-300 nm, such as 100 nm, 150 nm, 200 nm, 250 nm, or 300 nm.
[0011] Preferably, the particle size of the composite material is 1.5 to 50 μm, such as 1.5 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm.
[0012] Preferably, the diameter of the Cu-BTC crystal in the composite material is 0.5 to 48 μm, such as 0.5 μm, 4 μm, 9 μm, 14 μm, 19 μm, 24 μm, 29 μm, 34 μm, 39 μm, 44 μm, or 48 μm.
[0013] Preferably, the Cu-BTC crystal is an octahedral crystal.
[0014] Preferably, the composite material exhibits structural stability and good thermal stability in environments below 350°C.
[0015] Preferably, the spherical porous carbon is prepared by a method comprising the following steps: a second hydrothermal reaction of glucose aqueous solution to obtain spherical non-porous carbon, and calcination to obtain the spherical porous carbon.
[0016] More preferably, the reaction product is post-treated after the second hydrothermal reaction, the post-treatment including the separation of spherical non-porous carbon. More preferably, the post-treatment further includes washing and / or drying the separated spherical non-porous carbon, the washing solution being ethanol and / or water.
[0017] More preferably, the reaction temperature of the second hydrothermal reaction is 150–200°C. For example, it can be 150°C, 160°C, 170°C, 180°C, 190°C, or 200°C.
[0018] More preferably, the reaction time of the second hydrothermal reaction is 2 to 4 hours. For example, it can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, or 4 hours.
[0019] More preferably, the calcination temperature is 750–850°C. For example, it can be 750°C, 770°C, 790°C, 810°C, 830°C, or 850°C.
[0020] More preferably, the calcination time is 1 to 3 hours. For example, it can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, or 3 hours.
[0021] The second aspect of the present invention discloses a method for preparing a composite material, wherein a mixed solution for forming Cu-BTC is subjected to a first hydrothermal reaction with spherical porous carbon to obtain the composite material.
[0022] Preferably, the mixed solution for forming Cu-BTC is prepared by a method comprising the steps of dissolving PVP, H3BTC and Cu(NO3)2 in an aqueous ethanol solution.
[0023] More preferably, the mass ratio of Cu(NO3)2 to H3BTC is 1:(1-3).
[0024] More preferably, the mass ratio of Cu(NO3)2 to PVP is 1:(1-3).
[0025] Preferably, the molar ratio of C in the spherical porous carbon to Cu in the mixed solution used to form Cu-BTC is 1:(1-2). Increasing the amount of spherical porous carbon will also increase the thickness of the porous spherical carbon in the composite material.
[0026] Preferably, the reaction temperature of the first hydrothermal reaction is 90–150°C. For example, it can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, or 150°C.
[0027] Preferably, the reaction time of the first hydrothermal reaction is 9 to 15 hours. For example, it can be 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, or 15 hours.
[0028] Preferably, the first hydrothermal reaction is followed by separation and drying.
[0029] The third aspect of the present invention also discloses the use of the composite material as an adsorbent material as described above.
[0030] Preferably, the use is for separating isomers. More preferably, the isomer is phenylisopropylamine.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] In this invention, the inventors address the problems of poor water resistance, low ion exchange capacity, weak separation ability of drug isomers, and short retention time of traditional SiO2 adsorbent materials by using MOFs as adsorbent materials. Simultaneously, to address the technical issues of MOF materials being prone to local or overall collapse in the liquid phase and having poor dynamic adsorption efficiency, the applicant provides a composite material, its preparation method, and its applications. The composite material is a Cu-BTC crystal with spherical porous carbon composited on its surface, exhibiting high molecular recognition, high selectivity, high adsorption capacity, high water resistance, and environmental friendliness. The preparation process is simple, economical, and environmentally friendly, meeting the needs of research and application. Attached Figure Description
[0033] Figure 1 The N2 adsorption-desorption isotherms of the adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-2 of this invention are shown.
[0034] Figure 2 The images shown are SEM images of the adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-2 of this invention.
[0035] Figure 3 The images show the TG curves of the adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-2 of this invention.
[0036] Figure 4 This is a SEM image of the Cu-BTC prepared in Comparative Example 1 of this invention after water resistance testing.
[0037] Figure 5 The image shows the SEM image of Cu-BTC@SPC(1) prepared in Example 1 of this invention after water resistance testing.
[0038] Figure 6 The image shows the SEM image of Cu-BTC@SPC(2) prepared in Example 2 of this invention after water resistance testing.
[0039] Figure 7 The images show the XRD patterns of the adsorbent materials prepared in Examples 1-2 and Comparative Example 1 after water resistance testing.
[0040] Figure 8 The chromatogram is of Cu-BTC@SPC(1) prepared in Example 1 of this invention. Detailed Implementation
[0041] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.
[0042] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the respective manufacturers.
[0043] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or equivalent to those described, apparatus, and materials in the embodiments of this invention may be used to implement the present invention.
[0044] In this application, the applicant addresses the problems of poor water resistance, low ion exchange capacity, weak separation ability of drug isomers, and short retention time of traditional SiO2 adsorbent materials by using MOFs as adsorbent materials. Simultaneously, to address the technical issues of MOF materials being prone to local or overall collapse in the liquid phase and having poor dynamic adsorption efficiency, the applicant provides a composite material, its preparation method, and its applications. This composite material possesses high molecular recognition, high selectivity, high adsorption capacity, high water resistance, and is environmentally friendly; the preparation process is simple, economical, and environmentally friendly, meeting research and application needs.
[0045] In the following specific embodiments, the method for preparing the composite material is as follows:
[0046] S1. Preparation of spherical porous carbon;
[0047] S2. Dissolve Cu(NO3)2, PVP, and H3BTC in an aqueous ethanol solution to obtain a mixed solution;
[0048] S3, a mixed solution and a certain amount of spherical porous carbon undergo a hydrothermal reaction;
[0049] S4. Filter and dry the product after the hydrothermal reaction.
[0050] The performance indicators of the composite materials in this application are as follows:
[0051] 1) The specific surface area of the composite material is 900–1500 m². 2 / g;
[0052] 2) The average pore size of the composite material is 0.5–1.1 nm;
[0053] 3) The pore volume of the composite material is 0.5–0.6 cm. 3 / g;
[0054] 4) The particle size of each individual spherical porous carbon is 100–300 nm;
[0055] 5) The particle size of the composite material is 1.5–50 μm;
[0056] 6) The diameter of the Cu-BTC crystals in the composite material is 0.5–48 μm;
[0057] 7) The Cu-BTC crystal is an octahedral crystal.
[0058] Example 1
[0059] The specific processing method of the adsorbent material in this embodiment includes the following steps:
[0060] 1) Add 11.89 g of glucose to 30 mL of deionized water and sonicate the mixture for 5 minutes to obtain a clear and transparent solution;
[0061] The resulting clear solution was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 180 °C for 3 h.
[0062] The product after the reaction was washed six times with anhydrous ethanol and deionized water alternately, and then dried in a vacuum drying oven at 100℃ for 10 h to prepare spherical non-porous carbon.
[0063] Then, spherical non-porous carbon was calcined at 800°C for 2 hours in a tube furnace under N2 conditions to prepare spherical porous carbon.
[0064] 2) Dissolve 0.75g PVP in 30mL ethanol solution at 25℃, stir for 10min, then add 0.84g H3BTC, stir for 10min to obtain solution A;
[0065] Dissolve 0.84g Cu(NO3)2·3H2O in 30mL of deionized water and stir for 5min to obtain solution B;
[0066] 3) Pour solution B into solution A and continue stirring for 10 minutes. Then add 1.5 g of spherical porous carbon to the mixed solution, stir for 5 minutes, and sonicate for 10 minutes.
[0067] 4) Transfer the mixed solution to a polytetrafluoroethylene autoclave and react at 120°C for 12 hours.
[0068] 5) The product after the reaction is filtered and dried under vacuum at 150°C for 6 hours.
[0069] The adsorbent material obtained in this embodiment is Cu-BTC@SPC(1).
[0070] Example 2
[0071] The difference from Example 1 is that the amount of spherical porous carbon used is 2g, and the adsorbent material obtained in this example is Cu-BTC@SPC(2).
[0072] Example 3
[0073] The difference from Example 1 is that the amount of PVP used is 0.85g, the amount of H3BTC used is 0.95g, the amount of Cu(NO3)2·3H2O used is 0.95g, the amount of spherical porous carbon used is 3g, and the adsorbent material obtained in this example is Cu-BTC@SPC(3).
[0074] Comparative Example 1
[0075] The preparation method of the adsorbent material in this comparative example includes the following steps:
[0076] 1) Dissolve 0.84g H3BTC and 0.75g PVP in 30mL ethanol solution at 25℃ and stir for 10min to obtain solution A;
[0077] 2) Dissolve 0.84g Cu(NO3)2·3H2O in 30mL of deionized water and stir for 5min to obtain solution B;
[0078] 3) Pour solution B into solution A and continue stirring for 10 minutes. Then transfer the mixed solution to a polytetrafluoroethylene autoclave and react at 120°C for 12 hours.
[0079] 4) The product after the reaction is filtered and dried under vacuum at 150°C for 6 hours.
[0080] In this comparative example, the adsorbent material is Cu-BTC.
[0081] Comparative Example 2
[0082] The preparation method of the adsorbent material in this comparative example includes the following steps:
[0083] 1) Add 11.89 g of glucose to 30 mL of deionized water and sonicate the mixture for 5 minutes to obtain a clear and transparent solution.
[0084] 2) Transfer the obtained clear solution to a 100 mL polytetrafluoroethylene reactor and react at 180 °C for 3 h.
[0085] 3) The product after the reaction was washed six times with anhydrous ethanol and deionized water alternately, and dried in a vacuum drying oven at 100℃ for 10h to prepare spherical non-porous carbon.
[0086] 4) Then, the spherical non-porous carbon is calcined at 800°C for 2 hours in a tube furnace under N2 conditions to prepare spherical porous carbon.
[0087] In this comparative example, the adsorbent material is spheric porous carbon.
[0088] The adsorbent materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested, and their various properties are as follows:
[0089] 1) According to the appendix Figure 1 It can be calculated that the specific surface area of the Cu-BTC@SPC(1) is 1175 m². 2 / g, the Cu-
[0090] The specific surface area of BTC@SPC(2) is 1151 m². 2 / g, the specific surface area of the Cu-BTC@SPC(3) is 958
[0091] m 2 / g, the specific surface area of the Cu-BTC is 1460m². 2 / g, the specific surface area of the spheric porous carbon is 589m². 2 / g;
[0092] 2) According to the appendix Figure 1 It can be calculated that the average pore size of the Cu-BTC@SPC(1) is 1.017 nm, and the Cu-
[0093] The average pore size of BTC@SPC(2) is 0.971 nm, the average pore size of Cu-BTC@SPC(3) is 1.1092 nm, the average pore size of Cu-BTC is 0.524 nm, and the average pore size of Spheric porous carbon is 1.168 nm.
[0094] 3) According to the appendix Figure 1 It can be calculated that the pore volume of the Cu-BTC@SPC(1) is 0.506 cm³. 3 / g, the Cu-
[0095] The aperture volume of BTC@SPC(2) is 0.559 cm³. 3 / g, the pore volume of the Cu-BTC@SPC(3) is 0.552cm³. 3 / g, the pore volume of the Cu-BTC is 0.566cm³. 3 / g, the pore volume of the spheric porous carbon is 0.344 cm³. 3 / g;
[0096] 4) According to SEM testing, the particle size of the spherical porous carbon raw material in Cu-BTC@SPC(1) is 115-226 nm, the particle size of the spherical porous carbon raw material in Cu-BTC@SPC(2) is 140-274 nm, and the particle size of the spherical porous carbon raw material in Cu-BTC@SPC(3) is 174-295 nm.
[0097] 5) In the appendix Figure 2 The image shown in section (a) is a SEM image of spherical porous carbon, section (b) is a SEM image of Cu-BTC, section (c) is a SEM image of Cu-BTC@SPC(1), section (d) is a SEM image of Cu-BTC@SPC(2), and section (e) is a SEM image of Cu-BTC@SPC(3). Figure 2 It can be seen that the particle size of Cu-BTC@SPC(1) is 1.5-10 μm, the particle size of Cu-BTC@SPC(2) is 1.7-11 μm, the particle size of Cu-BTC@SPC(3) is 2.2-12 μm, the particle size of Cu-BTC is 2.4-9 μm, and the particle size of Spheric porouscarbon is 112-208 nm.
[0098] 6) SEM testing revealed that the diameter of the Cu-BTC crystal in Cu-BTC@SPC(1) was 1–9 μm, the diameter of the Cu-BTC crystal in Cu-BTC@SPC(2) was 1.5–10.5 μm, and the diameter of the Cu-BTC crystal in Cu-BTC@SPC(3) was [not specified].
[0099] The diameter of BTC crystals ranges from 0.9 to 11 μm.
[0100] 7) As attached Figure 2 As shown, in Example 1, Cu-BTC@SPC(1) has a regular octahedral crystal form; in Example 2, Cu-BTC@SPC(2) has a regular octahedral crystal form; and in Example 3, Cu-BTC has a regular octahedral crystal form.
[0101] In BTC@SPC(3), Cu-BTC is in the octahedral crystal form, as described in Comparative Example 1;
[0102] 8) As attached Figure 3As shown, the Cu-BTC@SPC(1) described in Example 1 is structurally stable in an environment below 350°C, and its weight loss rate is 62% above 350°C; the Cu-BTC@SPC(2) described in Example 2 is structurally stable in an environment below 350°C, and its weight loss rate is 57% above 350°C; the Cu-BTC@SPC(3) described in Example 3 is structurally stable in an environment below 350°C, and its weight loss rate is 51% above 350°C; the Cu-BTC described in Comparative Example 1 has a weight loss rate of 66% above 350°C.
[0103] Application Example 1
[0104] Excsep was performed using Cu-BTC@SPC(1) prepared in Example 1. TM C18 column packing test includes the following steps:
[0105] 1) Prepare a mobile phase by mixing methanol and water in a mass ratio of 75:25.
[0106] 2) Prepare the test target.
[0107] Prepare 25 μg / ml phenylisopropylamine, 200 μg / ml phenol, and 850 μg / ml toluene using the mobile phase as the solvent.
[0108] 3) Using a Waters liquid chromatograph and a 2487 detector, the flow rate was set to 1.0 ml / min, the detection wavelength to 254 nm, the column temperature to 23 °C, and the injection volume to 10 μl.
[0109] As shown in the attached test results. Figure 8 As shown:
[0110] 1) The retention time of D-phenylisopropylamine was 2.647 min, the tailing factor was 1.22, and the sample concentration after the test was 5 μg / ml;
[0111] 2) The retention time of L-phenylisopropylamine was 6.007 min, the tailing factor was 1.10, and the sample concentration after the test was 25 μg / ml.
[0112] 3) The retention time of phenol was 3.484 min, the tailing factor was 1.09, and the sample concentration after the test was 200 μg / ml.
[0113] 4) The retention time of toluene was 8.619 min, the tailing factor was 1.05, and the sample concentration after the test was 850 μg / ml.
[0114] It can be seen that Cu-BTC@SPC(1) prepared in Example 1 has good molecular recognition and can simultaneously adsorb different test targets.
[0115] Application Example 2
[0116] The water resistance of the adsorbents prepared in Examples 1, 2, and 1 (Cu-BTC@SPC(1), Cu-BTC@SPC(2), and Cu-BTC) was tested as follows:
[0117] The adsorbent materials prepared in Example 1, Example 2 and Comparative Example 1, namely Cu-BTC@SPC(1), Cu-BTC@SPC(2) and Cu-BTC, were soaked in deionized water at pH 7 for 24 hours.
[0118] The adsorbent materials prepared in Example 1, Example 2 and Comparative Example 1, namely Cu-BTC@SPC(1), Cu-BTC@SPC(2) and Cu-BTC, were soaked in hydrochloric acid aqueous solution with pH=2 for 24 hours respectively.
[0119] The adsorbent materials prepared in Example 1, Example 2 and Comparative Example 1, namely Cu-BTC@SPC(1), Cu-BTC@SPC(2) and Cu-BTC, were immersed in an aqueous sodium hydroxide solution with pH=12 for 24 hours.
[0120] The adsorbent materials prepared in Example 1, Example 2 and Comparative Example 1, namely Cu-BTC@SPC(1), Cu-BTC@SPC(2) and Cu-BTC, were immersed in water at 100°C for 2 hours.
[0121] The appendix Figure 4 (a1) is a SEM image of Cu-BTC after soaking in deionized water at pH=7 for 24 hours; (a2) is a SEM image of Cu-BTC after soaking in hydrochloric acid solution at pH=2 for 24 hours; (a3) is a SEM image of Cu-BTC after soaking in sodium hydroxide solution at pH=12 for 24 hours; and (a4) is a SEM image of Cu-BTC after soaking in water at 100℃ for 2 hours.
[0122] The appendix Figure 5 (b1) is a SEM image of Cu-BTC@SPC(1) after being soaked in deionized water at pH=7 for 24 hours; (b2) is a SEM image of Cu-BTC@SPC(1) after being soaked in hydrochloric acid solution at pH=2 for 24 hours; (b3) is a SEM image of Cu-BTC@SPC(1) after being soaked in sodium hydroxide solution at pH=12 for 24 hours; and (b4) is a SEM image of Cu-BTC@SPC(1) after being soaked in water at 100℃ for 2 hours.
[0123] The appendix Figure 6(c1) is a SEM image of Cu-BTC@SPC(2) after being soaked in deionized water at pH=7 for 24 hours; (c2) is a SEM image of Cu-BTC@SPC(2) after being soaked in hydrochloric acid solution at pH=2 for 24 hours; (c3) is a SEM image of Cu-BTC@SPC(2) after being soaked in sodium hydroxide solution at pH=12 for 24 hours; and (c4) is a SEM image of Cu-BTC@SPC(2) after being soaked in water at 100℃ for 2 hours.
[0124] The appendix Figure 7 In the figures, (a) shows the XRD patterns of Cu-BTC after being soaked in deionized water with pH=7, hydrochloric acid aqueous solution with pH=2, and sodium hydroxide aqueous solution with pH=12 for 24 hours and then boiled in aqueous solution at 100℃ for 2 hours; (b) shows the XRD patterns of Cu-BTC@SPC(1) after being soaked in deionized water with pH=7, hydrochloric acid aqueous solution with pH=2, and sodium hydroxide aqueous solution with pH=12 for 24 hours and then boiled in aqueous solution at 100℃ for 2 hours; and (c) shows the XRD patterns of Cu-BTC@SPC(2) after being soaked in deionized water with pH=7, hydrochloric acid aqueous solution with pH=2, and sodium hydroxide aqueous solution with pH=12 for 24 hours and then boiled in aqueous solution at 100℃ for 2 hours.
[0125] The following results were obtained from the test:
[0126] a) As attached Figure 5 SEM image and appendix Figure 7 As shown in the XRD results, after the water resistance test, the characteristic diffraction peaks of Cu-BTC@SPC(1) in Example 1 remained unchanged, and the appearance structure was basically intact.
[0127] b) As attached Figure 6 SEM image and appendix Figure 7 As shown in the XRD results, after the water resistance test, the characteristic diffraction peaks of Cu-BTC@SPC(2) in Example 2 remained unchanged, and the appearance structure was basically intact.
[0128] c) As attached Figure 4 SEM image and appendix Figure 7 The XRD results show that after the water resistance test, the characteristic diffraction peaks of Cu-BTC in Comparative Example 1 did not change, but the appearance structure was basically destroyed.
[0129] It is evident that porous spherical carbon has a protective effect on crystal morphology, and the composite material exhibits high water resistance.
[0130] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. The use of a composite material as an adsorbent, characterized in that, The purpose is to separate isomers, the isomer being phenylisopropylamine; the composite material is porous particles, the porous particles being Cu-BTC crystals with spherical porous carbon composited on the surface; The composite material was prepared by subjecting a mixed solution for forming Cu-BTC to a first hydrothermal reaction with spherical porous carbon. The molar ratio of C in the spherical porous carbon to Cu in the mixed solution used to form Cu-BTC is 1:(1~2); the reaction temperature of the first hydrothermal reaction is 90~150℃; and the reaction time of the first hydrothermal reaction is 9~15h.
2. The use as described in claim 1, characterized in that, The specific surface area of the composite material is 900~1500 m². 2 / g; And / or, the average pore size of the composite material is 0.5~1.1 nm; And / or, the pore volume of the composite material is 0.5~0.6 cm. 3 / g; And / or, the particle size of a single spherical porous carbon is 100~300 nm; And / or, the particle size of the composite material is 1.5~50µm; And / or, the diameter of the Cu-BTC crystals in the composite material is 0.5~48µm; And / or, the Cu-BTC crystal is an octahedral crystal.
3. The use as described in claim 1, characterized in that, The spherical porous carbon is prepared by a method comprising the following steps: a second hydrothermal reaction is carried out in an aqueous glucose solution to obtain spherical non-porous carbon, and calcination is performed to obtain the spherical porous carbon.
4. The use according to claim 3, characterized in that, The reaction product is post-processed after the second hydrothermal reaction. The post-processing includes separating spherical non-porous carbon and further includes washing and / or drying the separated spherical non-porous carbon. The washing solution is ethanol and / or water. And / or, the reaction temperature of the second hydrothermal reaction is 150~200℃; And / or, the reaction time of the second hydrothermal reaction is 2-4 hours; And / or, the calcination temperature is 750~850℃; And / or, the calcination time is 1 to 3 hours.
5. The use according to claim 1, characterized in that, The mixed solution used to form Cu-BTC is prepared by a method comprising the following steps: dissolving PVP, H3BTC and Cu(NO3)2 in an aqueous ethanol solution.
6. The use according to claim 5, characterized in that, The mass ratio of Cu(NO3)2 to H3BTC is 1:(1~3); and / or, the mass ratio of Cu(NO3)2 to PVP is 1:(1~3).
7. The use according to claim 1, characterized in that, The first hydrothermal reaction is followed by separation and drying.